Oulu Biovillage: Exploring Blue Bioeconomy Ecosystem Opportunities in Oulu, Finland - Lex,Emeline (2019)
By the year 2030, the world will need 50% more food, 45% more energy and 30% more water. This growth in demand will increase pressure on our natural resources. Ingenuitive and adaptive thinking will therefore be required in the ways we build our cities. Finland, with its abundance of natural resources: its forest, its lakes and its aquatic resources, as well as its expertise in sustainable resource use and development, has strategically placed itself as a pioneer in transitioning its economy from one reliant on fossil fuels into one which harnesses the full potential of renewable natural resources and unlocks the full potential waste: creating food, energy, products, services, and jobs in line with sustainable development. The project explores this opportunity further in Oulu, Finland; where one of mainland Finland’s largest fish farms is being planned north of the city in Haukipudas. The project examines the potential of creating a fully-functional blue bioeconomy ecosystem, unlocking the full potential of sidestreams and waste, and exploring the synergies between fish, food, and energy production into a self-sustaining bio-district. The project seeks to integrate production activities: fish, vegetable produce, services, new industrial products; with everyday life, to enhance the relationship of citizens with nature and linking consumption with production.
Keywords: Bioeconomy; blue bioeconomy; circular economy; ecosystem; waste-to-resource systems; local; community; regenerative; fish; aquaculture; renewable energies; biogas; bioenergy; live-work; cradle-to-cradle; typologies; greenhouse; environment; business; Oulu; Finland